Effects of prosody awareness training on consecutive interpreting from english into vietnamese: an experimental study = Ảnh hưởng của khóa học nâng cao nhận thức về “vần-nhịp-điệu” trong dịch ứng đoạn Anh – Việt: nghiên cứu thực nghiệm - Ngô, Thị Hoài Thu (2020)
Despite of the utmost importance in decoding the input and encoding the output, prosody has been marginalized in many interpreting programs and the curriculum in University of Language and International Studies (ULIS, VNU) is not an exception. Therefore, it urged the researcher to conduct an experimental research employing quantitative method to assess the effectiveness of prosody awareness training on consecutive interpreting from English into Vietnamese. The experiment was conducted with the participation of 6 third-year students majoring in translation and interpreting in FELTE, ULIS. Before a training program began, a questionnaire was delivered to 231 third-year and fourth-year students to enquire their awareness to the influence of prosodic features on consecutive interpreting performance and their attention to those features in interpreting practice. The findings indicated that both seniors and juniors were aware of the importance of prosody, and yet the majority of them seemed surprised at the fact that prosody could be trained in order to boost interpreting performance. Regarding the results of prosody training program, though not making prosody learners far better in overall performance of consecutive interpreting in comparison with those who did not receive training, it did help them to gain improvements in prosodic features such as pace and voice. Therefore, this study would serve as a reference for teachers and syllabus designers to introduce prosody into the syllabus of interpreter trainees at ULIS, VNU in the future.